박테리아 혼합물 - SPOTO MICHELLE; ZHOU WEI; OH JULIA (2022)
본 개시내용은 병독성 인자 유전자 및 병독성에 기여하는 다른 유전자, 예컨대 질소 호흡 유전자, 우레아제 활성 유전자, 탄수화물 대사 유전자, 철 흡수 유전자, 황 대사 유전자의 발현을 변형시킬 수 있는 에스. 에피더미디스 유형 I 세포, 에스. 에피더미디스 유형 II 세포, 에스. 에피더미디스 유형 III 세포, 에스. 에피더미디스 유형 IIIb 세포, 및 에스. 에피더미디스 유형 IV 세포로부터 선택된 스타필로코커스 (에스.) 에피더미디스 세포의 혼합물을 제공한다. 본 개시내용은 또한 에스. 에피더미디스 세포 유형의 혼합물을 투여함으로써 대상체에서 피부 질환을 치료 또는 예방하고, 재발성 피부 질환의 위험을 감소시키는 방법을 제공한다. The present disclosure provides an admixture of Staphylococcus (S.) epidermidis cells selected from S. epidermidis Type I cells, S. epidermidis Type II cells, S. epidermidis Type III cells, S. epidermidis Type Mvb cells, and S. epidermidis Type IV cells capable of modified expression of virulence factor genes and other genes that contribute to virulence, such as nitrogen respiration genes, ureases activity genes, carbohydrate metabolism genes, iron uptake genes, sulfur metabolism genes. The present disclosure also provides methods of treating or preventing skin disease and reducing the risk of recurrent skin disease in a subject by administering the admixtures of S. epidermidis cell types.